ARÁN, Olga Pampa. Nuevo diccionario de la teoría de Mijail Bajtin. Córdoba, Argentina: Ferreyra Editor, 2006. 284p. - Pistori, Maria Helena Cruz (Bakhtiniana. Revista de Estudos do Discurso, 2012)
Resenha